Synthesis, structure elucidation and selected biological activities of Ag(I) and Au(I) complexes constructed from thiosemicarbazone and phosphine ligands / Syahrina Nur ‘Ain Abdul Halim - Syahrina Nur ‘Ain , Abdul Halim (2020)
New Ag(I) and Au(I) mixed ligand complexes were synthesised using thiosemicarbazone and phosphine in search of a new biologically active compounds. CHN elemental analysis, powder X-ray diffraction (PXRD), single crystal X-ray diffraction as well as several spectroscopic techniques such as FT-IR, Energy-dispersive X-ray (EDX), 1H, 13C, and 31P{1H} NMR were performed to elucidate the structure of these complexes. Elemental analysis suggested that the stoichiometry of the complexes formed by the reaction of Ag nitrate with thiosemicarbazone in the presence of phosphine was indeed 1:2:1 molar ratio, while for the Au to be in 1:1:1 molar ratio. The Ag and Au were discovered to be coordinated to the sulphur of thiosemicarbazone and phosphorus of phosphine, having a tetrahedral and linear geometry respectively. The in-vitro antiproliferative activity of these Ag(I) complexes was investigated towards the MDA-MB-231 and MCF-7 breast cancer cell lines, as well as the HT-29 colon cancer cell line, which yielded IC50 values in low micromolar range. The antiplasmodial activity of these Ag complexes was also examined against chloroquine-resistant P. falciparum parasite which demonstrated good activity and further tested for their selectivity index. As for the Au(I) complexes and its free ligands, their antibacterial activity were tested against E. coli and S. aureus and the result shown that the ligands exhibited higher activity. Preliminary results of transforming the gold complexes to metal clusters by chemical reduction are also discussed in this thesis.